Vladimir Grigoryevich Shuchov – engineer-inventor of genijus, creator of Stanislav-Adziogol lighthouses - O. V. Sandurska (History of science and technology, 2015)
Inthearticlethe characteristic of main biographical data of Vladimir Grigoryevich Shukhovisgiven. The author of the article outlines hiskeyachie vementsint hearea of railwayandpipe line transport, raising bridges and electricity transmissiontowers, and also considers the inventor’sunique reticulate construction and its use in building different engineering structures. Special attentionispaidto V.G. Shukhovcreating  Stanislav-Adzhiogol Lighthouse – one of the highest lighthouses in Europe. Also, the author determines the role of lighthouses in navigation.